Sillaginid fishes of Palk Bay and Gulf of Mannar with an account on the maturation and spawning of Indian sand whiting, Sillago sihama (Forsskal)* - Jayasankar, P (Indian Journal of Fisheries, 2011)
In the Palk Bay and Gulf of Mannar 6 species of the family Sillaginidae occurred: Sillago (Sit.faginopodys) chondropus. Silfago (Silfago) sihama. Sil/ago (Sil/ago) indica, Sil/ago (Parasillago) vinÂ·centi, Sillago (Parasillago) argentifasciata and Silfago (ParasiUago) soringa, A key to the idenLificaLionof these species is given and their morphometric and meristic characters tabulated. S. ~ihama, the mOSLdominant sillaginid species in this region, was a prolonged breeder. The spawning season of Lhis speciesextended from July to February, with peak spawning activity durinll July to November. Lengths aL firstmaturity of females and males were 179 and 159 mm respectively. Fecundity varied from 6956 to 48373and showed. high correlation with length, body weight and ovary weight of the fish, Overall sex ratioindicated predominance of females. Length-related sex ratio showed significant dominance of males tin170 mm and that of females above this length.